Bench Mark Survey Report Kolhapur Project-Bombay - Planning Commission (Planning Commission, 1956)
Among the objectives of evaluation work undertaken by the Programme Evaluation Organisation, two of the more important arc (i) assessment of the extent of adoption of improved practices advocated by the community development and national extension programmes and (ii) obtaining detailed insight into the impact of these programmes upon the economic and social life of the rural people. The field officers of the organisation had been making observations on these two aspects in their periodic reports from the time they were posted in the field in May 1953. However, considering the importance of detailed and precise information on these aspects for a proper appreciation of the development programmes it was felt that a special survey should be undertaken in all the evaluation centres for his purpose.
Government of India Planning Commission Programme Evaluation Organisation